ANALYSIS OF MACKEREL RAW MATERIAL INVENTORY IN MICRO, SMALL, AND MEDIUM SCALE FISH MILLING IN BENGKULU CITY - Ariandini, Rantika; Reswita, Reswita; Sukiyono, Ketut; Rahayu, Heni Sulistiawati Purwaning (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
This study examines raw material inventory control in micro, small, and medium-scale fish milling businesses in Bengkulu City, focusing on mackerel as the primary raw material. Mackerel is highly perishable and affected by seasonal and weather factors, requiring careful supply planning. The research location was selected purposively based on Law Number 20 of 2008. The study aims to determine optimal inventory control using the EOQ method, as well as safety stock and reorder points (ROP). The results show that the optimal order quantity per period is 894 kg for micro-scale, 1,617 kg for small-scale, and 1,870 kg for medium-scale businesses. Additionally, the total inventory cost using the EOQ method is lower than the company's existing approach, making it a more efficient option for managing raw material supplies.